A decision support system for upper limb rehabilitation robot based on hybrid reasoning with RBR and CBR - Li, Sujiao; Xiang, Shuhan; Ma, Qiqi; Cai, Wenqian; Liu, Suiyi; Fang, Fanfu; Yu, Hongliu (Frontiers in Bioengineering and Biotechnology, 2024)
The rehabilitation robot can assist hemiplegic patients to complete the training program effectively, but it only focuses on helping the patient's training process and requires the rehabilitation therapists to manually adjust the training parameters according to the patient's condition. Therefore, there is an urgent need for intelligent training prescription research of rehabilitation robots to promote the clinical applications. This study proposed a decision support system (DSS) for the training of upper limb rehabilitation robot based on hybrid reasoning with rulebased reasoning (RBR) and case-based reasoning (CBR). The expert knowledge base of this system is established base on 10 professional rehabilitation therapists from three different rehabilitation departments in Shanghai who are enriched with experiences in using desktopbased upper limb rehabilitation robot. The RBR is chosen to construct the cycle plan inference model, which develops a 21-day training plan for the patients. The case base consists of historical case data from 54 stroke patients who underwent rehabilitation training with a desktop-based upper limb rehabilitation robot. The CBR, combined with a Random Forest optimized algorithm, was constructed to adjust the training parameters for the patients in real-time. The system recommended a rehabilitation training program with an average accuracy of 91.5%, an average AUC value of 0.924, an average recall rate of 88.7%, and an average F1 score of 90.1%. The application of this system in rehabilitation robot would be useful for therapists.